Characterization of autochthonous lactic acid bacteria from an artisanal Italian cheese - Zeppa, Giuseppe (Acta agriculturae Slovenica, 2004)
We studied the natural lactic bacteria population of an artisanal Italian cheese, Toma piemontese POD, from Piedmont (Northwest Italy), in order to select new strains to be used as starters in large-scale production. Isolates collected from curd and ripened artisanal cheeses were identified by the combined use of PCR 16S-23S rDNA spacer analysis, species-specific probes and 16S rDNA sequencing. Lactococci constitued 67% of the coccal isolates. Enterococci were also isolated together with strains of Streptococcus macedonicus and S. thermophilus. Lactobacilli were only detected in three samples of curds. Acidification and proteolytic activity and aroma production were also determined for each isolate. On the basis of the results a few isolates were selected and used as starters in cheesemaking trials with both raw and pasteurised milk. The produced cheeses were sensory evaluated and two of them showed typical Toma piemontese taste and flavour. The results suggest the possibility to use these new starters in both dairy industry and artisanal cheesemaking to improve product quality.
Keywords: mlečni izdelki; sir; microbiology; mikrobiologija; mlečnokislinske bakterije; Italija; Italy